Artificial intelligence for medical writing in doctors of Punjab; a cross-sectional study - Iram Manzoor; Nasir, Mehreen; Ghulam Rasool; Aleem Ullah Qureshi; Zainab Rehman; Zahid Iqbal (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the frequency and perceptions regarding the use of artificial intelligence in medical writing among doctors. Method: The analytical, cross-sectional study was conducted from July to September 2023 in Punjab, Pakistan, after approval for the ethics review board of Akhtar Saeed Medical and Dental College, Lahore and comprised serving doctors with at least two publications during the study period. Data was collected using a questionnaire that explored sociodemographic details, frequency of artificial intelligence usage, and the subjects’ perceptions regarding its use in medical writing. Data was analysed using SPSS 23. Results: Of the 445 respondents, 248(55.7%) were females and 197(44.3%) were males. The overall mean age was 38.7+/-10.91 years, and the number of mean publications was 6.82+/-10.2. Awareness level regarding use of artificial intelligence in medical writing was high 413(92.8%), with 110(24.7%) having already used it, and 368(82.7%) considering its use in the future. Concerns about confidentiality breaches was the most common barrier to using artificial intelligence 307(69%). Conclusion: About a quarter of the sample studied had used artificial intelligence for medical writing. Key Words: Artificial intelligence, Medical writing, AI in healthcare.